O TRABALHO DAS MULHERES DA AGRICULTURA FAMILIAR À INDÚSTRIA CAPITALISTA CONTEMPORÂNEA E A INCIDÊNCIA DOS MITOS NAS RELAÇÕES DE GÊNERO NA SOCIEDADE PATRIARCAL - Silse Teixeira de Freitas Lemos (Universidade Federal do Maranhão, 2016)
The intent of the study is to peer into a historical course of western cultural formation, the social space of the woman in the sphere of work, by the influence of myths and symbolisms of patriarchal society. Refers to the presentation of the meaning of myth and gender concepts established by Joan Scott. The literature of authors and classic situations about the theme are used to make the historical path of the work of women.